(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
This paper presents preliminary work to address concern over DSDV protocol in mobile adhoc network. Firstly, we discussed the scalability design issues with related work in context of mobile adhoc network (MANET). Following, we design the simulation scenario. Finally, significance of scalability on the behavior of application, MAC, Transport and Physical layer performance is described.